Mengasah Keterampilan Bahasa Anak Usia Dini Melalui Kegiatan Bernyanyi - Eka Rizki Amalia; Hasana Hasana (Aulada : Jurnal Pendidikan dan Perkembangan Anak, 2018)
During the children’s development, they will experience a phase called the golden age. This phase is the most crucial stage in children's development because they will grow and develop rapidly. This phase is the foundation for developing cognitive, motoric, socio-emotional, religious, moral and language abilities. Regarding the development of children's language skills, it will be optimal if it is conducted with stimulation from the surrounding both from the parents or family and the teachers. This literature study discusses the importance of directing and fostering the children’s language skills from early childhood and activities that can support the stimulation process of early childhood language skills. The results of the literature review show that children’s language skills must be directed and nurtured since early childhood. A person's language skills show his intelligence in expressing certain words and sentences regularly and precisely. For early childhood, the best stimulation is given by singing activities. Singing activities cannot be separated from social relations, both with the environment, society, friends, and family. By singing activities, children will be introduced to how to respect others, to put themselves in a new environment, and train their ability to communicate.